Designing DNA probe from HPV 18 and 58 in the E6 region for sensing element in the development of genosensor-based gold nanoparticles - Jaapar, F. Nadhirah; Parmin, Nor Azizah; A. Halim, N. Hamidah; Hashim, Uda; Gopinath, Subash Chandra Bose; Halim, F. Syakirah; A. Rahim, Ruslinda; Voon, C. H.; M. N., Afnan Uda; Sharifah Nadzirah; Rejali, Zulida; Mohd Jamil, Amilia Afzan; et al. (Wiley, 2021)
The E6 region has higher protuberant probability annealing than consensus probe focusing on another region in the human papillomavirus (HPV) genome in terms of detection and screening method. Here, we designed the first multiple virus single-stranded deoxyribonucleic acid (ssDNA) for multiple detections in an early phase of screening for cervical cancer in the E6 region and became a fundamental evolution of detection electrochemical HPV biosensor. Gene profiling of the virus ssDNA sequences has been carried by high-end bioinformatics tools such as GenBank, Basic Local Alignment Searching Tools (BLAST), and Clustal OMEGA in a row. The output from bioinformatics tools resulted in 100% of similarities between our virus ssDNA probe and HPV complete genome in the databases. The cross-validation between HPV genome and our designed virus ssDNA provided high specificity and selectivity during screening methods compared with Pap smear. The DNA probe for HPV 18, 5' COOH-GAT CCA GAA GGT ACA GAC GGG GAG GGC ACG 3', while 5'COOH-GGG CGC TGT GCA GTG TGT TGG AGA CCC CGA3' as DNA probe for HPV 58 designed with 66.77% guanine (G) and cytosine (C) content for both. Our virus ssDNA probe for the HPV biosensor promises high sensitivity, specificity, selectivity, repeatability, low fluid consumption, and will be useful in mini-size diagnostic devices for cervical cancer detection.